Dermoscopic findings in different clinical variants of lichen planus. Is dermoscopy useful? - Paula Friedman (Mattioli1885, 2015)
Lichen planus (LP) is a papulosquamous dermatosis that involves the skin, scalp, nails and mucous membranes. Although its pathogenesis is still unknown, there is evidence that an imbalance of immunologic cellular reactivity plays an important role. Histopathologic examination reveals characteristic interface dermatitis.